Iron Supplementation in the Prevention and Treatment of Iron Deficiency Anemia in Children Under Five: A Systematic Review: Iron Supplementation in the Prevention and Treatment of Iron Deficiency Anemia - Tahir, Tujza; Bari, Uzma; Zahra, Fatima Tuz; Tariq, Hafsa; Hussain, Faisal; Iqbal, Muhammad (Pakistan Journal of Health Sciences, 2026)
Iron deficiency anemia (IDA) is a public health issue in children under 5 years of age, mostly in low and middle-income countries. Iron supplements are given for preventing or treating iron deficiency. Objectives: To systematically evaluate the effectiveness, safety considerations, and implementation characteristics of iron supplementation strategies used for the prevention and treatment of iron deficiency anemia among children under five years of age. Methods: An electronic literature search was performed in PubMed, Scopus, and Cochrane Library for any studies written in English and published between 2019 and 2024. Primary human research of any type assessing iron supplementation in children aged 0-59 months was encompassed. This excluded systematic reviews, meta-analyses, case reports, and animal studies. The study selection was in accordance with PRISMA 2020. The synthesis of the data was conducted narratively, and the risk of bias was assessed using the RoB-2 and Joanna Briggs Institute tools. Results: A total of 15 studies reported significant improvements in hemoglobin levels and iron status after iron supplementation, using either oral ferrous preparations or iron-containing micronutrient powders. Prevention measures reduced the rate of anemia, and treatment supplementation successfully corrected known IDA. High anemia burden, inconsistent adherence to supplementation, and dietary iron deficit were observed in observational studies. Conclusions: Iron supplementation remains an effective approach for preventing and treating iron deficiency anemia in children. Optimizing program delivery, adherence, and safety monitoring is essential to maximize benefits, particularly in resource-limited settings.